Land And Building Tax (PBB) In Efforts To Increase Local Revenue In Lubuklinggau City - Ayub, Ayub; Sudarmiyati, Sudarmiyati; Zabad, Imam Alfairus (Universitas Dehasen Bengkulu, 2025)
This study is purposed to determine the optimization of land and building tax (PBB) collection in increasing regional revenue in terms of expanding the revenue base, strengthening the collection process, and improving supervision in the city of Lubuklinggau. This study employs a qualitative method, with the types and sources of data consisting of primary and secondary data. Primary data was obtained through observation and interviews, while secondary data was sourced from documentation related to the study. The data analysis techniques used in this study include data reduction, data display, and conclusion drawing/verification. The research results indicate that the optimization of Land and Building Tax (PBB) collection in Lubuklinggau City is not yet optimal. This is due to ineffective collection implementation and weak oversight. In terms of expanding the revenue base, efforts have been made optimally, as evidenced by the initiative of the Regional Revenue Agency (Bapenda) to collaborate with the Population and Civil Registration Office (Disdukcapil) for data synchronization, as well as collaboration with Bank Sumsel Babel and various other payment channels to facilitate the public in fulfilling their tax obligations. However, in terms of strengthening the collection process, implementation has not been maximized due to low taxpayer awareness and the lack of strict oversight and penalties for violators. Meanwhile, oversight aspects have also not been optimal due to the lack of routine monitoring and limited available oversight resources. These conditions have led to low taxpayer compliance rates, ultimately resulting in sub-optimal PBB revenue collection.